PEMBELAJARAN MATEMATIKA MENGGUNAKAN TEORI APOS DI PERGURUAN TINGGI - Nerly Khairani (Study Program of Mathematics Education of Unimed Postgraduate Program, 2008)
APOS theory (action, process, object, and schema learning is an approach that combines the use of computers in teaching and learning in groups (cooperative learning), this learning approach was developed by Ed Dubinsky and his colleagues are primarily intended for learning mathematics at university. On paper learning paradigm will be discussed based on the theory of APOS and several studies related to the theory of APOS.